In defense of ecosystems - Rolston, Holmes, 1932-2025, author; New York Botanical Garden, publisher (Colorado State University. Libraries, 1988)
Ethical concern has focused on the welfare of individuals--persons, animals, plants--but an environmental ethic is not complete without concern for the biotic community. This shift of focus can be defended with prudential reasons. At depth, however, the defense of ecosystems involves more moral courage. Human cultures emerged from Earth's ecosystems, remain tethered to them, and ought to respect creative evolutionary ecosystems, the systems of life.
Keywords: Endangered Species Act; ecosystems; environmental ethics; ecological ethics